Madoera Stoomtram Maatschappij: fungsi perkeretaapian sebagai pengangkutan garam hingga transportasi umum di Madura tahun 1897-1987 - Faniesa Ardianti Mahdiyar; Naning Siregar Pribumi; Sopia Nabila; Ari Sapto (Historiography: Journal of Indonesian History and Education, 2022)
Who would have thought that Madura Island, which was surrounded by the expanse of the Java Sea, used to have access to modern transportation, namely trains. The railway line in Madura had been built during the Dutch Colonial Government and its use developed over time. The use of trains during the Dutch colonial administration is known to have first functioned as transportation of local commodities, especially salt commodities, which was centered in Sumenep, then changed to public transportation that can be used by the surrounding community. As for the formulation of the problem to be discussed, the first is to find out the background of the founding of Madoera Stoomtram Maatschappij. Second, to find out the function of the train run by Madoera Stoomtram Maatschappij in salt transportation activities to become a means of public transportation in Madura. Then, the third, to find out the reason for Madoera Stoomtram Maatschappij's cessation of operations. The research method used is the historical research method. Siapa sangka jika Pulau Madura yang dikelilingi hamparan Laut Jawa dulunya memiliki akses transportasi modern, yakni kereta api. Jalur kereta api di Madura telah dibangun pada masa Pemerintahan Kolonial Belanda dan penggunaannya berkembang seiring berjalannya waktu. Penggunaan kereta api pada masa pemerintahan kolonial Belanda diketahui pertama kali berfungsi sebagai pengangkutan komoditas lokal, khususnya komoditas garam yang berpusat di Sumenep, kemudian berganti menjadi alat transportasi umum yang sudah bisa digunakan oleh masyarakat sekitar. Adapun rumusan masalah yang akan dibahas, yaitu pertama untuk mengetahui bagaimana latar belakang berdirinya Madoera Stoomtram Maatschappij. Kedua, untuk mengetahui fungsi kereta api yang dijalankan oleh Madoera Stoomtram Maatschappij dalam kegiatan pengangkutan garam hingga menjadi alat transportasi umum di Madura. Kemudian, yang ketiga, untuk mengetahui alasan berhenti operasinya Madoera Stoomtram Maatschappij. Metode penelitian yang digunakan adalah metode penelitian sejarah.